Examples of Orientalists' Views on the Holy Quran - Aldriwi, Manal Atia; Areebi, Asma Salem (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
This research aims to present various perspectives of orientalists regarding the Holy Quran. The Holy Quran has been a subject of interest for orientalists, and any criticism or doubt about it is often seen as criticism of Islam itself. The central question of this study is to understand the reasons behind the interest of orientalists in studying the Holy Quran and whether their approach is purely scientific. The study also seeks to explain the reasons for delving into the study of the Holy Quran in general and to highlight the true purpose behind raising questions about the arrangement of its chapters. The researcher employed historical and inductive methodologies, as well as descriptive and analytical approaches, to suit the nature of this study.
Keywords: Islam; Orientalists; Criticism; Doubt; Influence tendency